The syntax of Philippine-type alignment: Insights from case-marking - Chen, Victoria (Natural language and linguistic theory, 2025)
Despite the apparent hallmarks of syntactic ergativity found in Philippine-type Austronesian languages, a closer look at the distribution of three basic case markers reveals that their ergative characteristics are only illusory. Support for an accusative view firstly comes from the presence of the putative oblique case on ECM subjects, derived objects, and objects inside restructuring infinitives—a distribution that undermines the antipassive view of Philippine-type Actor Voice, indicating instead that the alleged antipassive features accusative object and does not alternate transitivity based on voice. Further evidence comes from the locality-constrained distribution of the putative inherent ergative case, which shows hallmarks of structural nominative and suggests that the extraction restriction imposed on these languages is distinct from the ban on ergative extraction. Finally, the nonlocal distribution of the so-called absolutive case reveals that it is a marker independent of case, in line with recent Ā-topic approaches to this marker. These observations motivate the view that ‘Philippine-type alignment’ reflects a nominative-accusative case system obscured by prominent topic-marking that overrides morphological case. This conclusion lends new support to the accusative view of Philippine-type languages and yields two implications: (i) highly constrained Ā-extraction asymmetry may be independent of syntactic ergativity, and (ii) discourse-configurational languages such as Philippine-type Austronesian languages may exhibit superficial traits of syntactic ergativity where topic-marking is imprecisely treated as part of their case system.